Nitrogen trade-offs between roots and leaves of Moso bamboo and different effects of management practices on root traits and processes in subtropical forests - Jiang, Junhui; Shi, Wenhui; Fu, Yu; He, Yuelin; Wang, Shuyang; Ying, Yeqing; Jiang, Lei (Frontiers in Plant Science, 2025)
Plant traits mediate resource acquisition strategies via trade-off between belowground root nutrient absorption and aboveground leaf nutrient resorption, yet mechanistic insights remain limited for clonal species like Moso bamboo (Phyllostachys edulis). This study was conducted in Moso bamboo plantations in Zhejiang Province, China. We measured rhizome-system absorptive roots, leaf properties, and soil nutrient contents to explore acquisition-resorption relationships. We also examined how management practices (abandonment [AM], conventional biennial [CM], and high-intensity annual plus understory planting [HM]) influence the traits and processes in Moso bamboo forests. Key novel findings include: (1) A consistent trade-off emerged for nitrogen [N] (negative relationships between root N absorption and leaf N resorption) but not phosphorus [P]. (2) Principal component analysis revealed root traits economics structured along two axes: first (PC1), specific root length [SRL]and root tissue density [RTD] (root lifespan) and second (PC2), cortex thickness [CT] and branching intensity [BI] (fungal independence). Interestingly, the PC1 was positively correlated with N absorption potential, and negatively correlated with N resorption efficiency. (3) HM significantly enhanced SRL (+75% vs. CM) and resorption efficiency (+23% for N, +37% for P), likely driven by interspecific competition under herb planting. While AM treatment showed relatively slight effects on traits and processes, compared with CM treatment. Our findings advance functional trait theory by decoding how clonal integration reconfigures traditional acquisition-resorption relationships, offering critical insights for bamboo forest management under global change and management.